THE IMPACT OF CONTINUOUS PROFESSIONAL DEVELOPMENT (CPD) ON SHIFTING TEACHER BELIEFS AND CLASSROOM PRACTICES IN STEM EDUCATION - Dewi Angreini Telaumbanua; Derliana Pane; Fatimah Siregar; Anita Adinda (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study investigates the impact of Continuous Professional Development (CPD) on shifting teacher beliefs and classroom practices in STEM education at SDN No. 100710 Hapesong Baru.. The research aimed to explore how sustained professional learning experiences contribute to teachers’ pedagogical transformation from content transmitters to learning facilitators. Employing a qualitative case study design, data were collected through classroom observations, semi-structured interviews, and document analysis involving four STEM teachers who participated in a year-long CPD program. The findings reveal that CPD fostered significant changes in teachers’ beliefs toward student-centered learning and encouraged more interactive, inquiry-based classroom practices. However, challenges such as limited institutional support and resource constraints still hindered full pedagogical implementation. The study highlights the importance of contextualized CPD programs in developing reflective and adaptive STEM educators, offering insights for policymakers and practitioners seeking to enhance teacher professionalism in developing-country contexts.